A framework for critical reflection in sport management education and graduate employability. Issue 2 (15th March 2018) - de Schepper, Jos; Sotiriadou, Popi
ABSTRACT: Sport management education is increasingly including opportunities for critical reflection in both formal and informal learning environments to improve graduate employability. This paper outlines potential reasons why there is disconnect between the skills employers want in the sport industry and the skills that sport management programmes equip graduates with. The findings of this review suggest that critical reflection in tertiary sport management education is individually oriented, and neglects the social dimensions and other contextual aspects (e.g. organizational culture) of the sport industry. This paper proposes an operationalization of critical reflection into three individual dimensions (experimentation, asking for feedback, and career awareness) and three social dimensions (challenging group-think, openness about mistakes, and sharing ideas). The paper concludes with suggestions for further research and higher education policy direction that combines formal and informal learning environments in enhancing the social aspects of critical reflection in sport management curricula.